Pesticide Emergencies: Contingency Planning - Frederick M. Fishel (EDIS)
In the event of a pesticide emergency, having an emergency response plan can help protect the health and welfare of employees and the community, minimize environmental damage, and potentially reduce liability. The goal of contingency planning is to prevent emergencies; but if an emergency does occur, the contingency plan allows business owners and managers to react appropriately in order to minimize detrimental effects. This 11-page fact sheet provides insight on how to develop a contingency plan for addressing emergencies where pesticides are involved. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.